Assessment of Structural Rebar Wastage of Reinforced Cement Concrete Buildings: A Case Study of School Building Type Designs in Kathmandu - Dahal, Sanjaya; Lamichhane, Govinda Prasad; Subedi, Safal (Pokhara Engineering College Journal, 2025)
Economic growth and urbanization in developing countries have led to significant construction activities, resulting in large amounts of waste, which is recognized as a key problem in various cities. In this regard, the management of waste is recommended as an important and integrated task in project execution. In this study, rebar waste generated from construction activities of educational building projects in Kathmandu is examined. A qualitative approach was followed, using four types of school building designs as case studies. Site observations, data collection, and analysis of the selected buildings were carried out. The minimum and maximum cutting waste of structural rebar were found to be 11.52% and 15.21%, respectively. The results of each project are presented, and a cross-case analysis was conducted to compare similarities and differences in factors related to waste generation.